Rate of detection of endocrine diseases in children in the practice of a family doctor - Redko, I. I.; Chakmazova, E. N. (Modern medical technology, 2020)
Introduction. In the context of the reform of modern medicine, endocrine pathology is encountered not only by pediatric endocrinologists, but also by doctors of other specialties, primarily primary care doctors pediatricians and family doctors. Currently, there is a tendency to increase the prevalence of endocrine pathologists in all age groups of the children's population of Ukraine. Purpose of the study. Assess the frequency and structure of endocrine pathology in children at the primary stage. Materials and methods. In the conditions of children's outpatient clinics 4273 children aged from 0 to 18 years were consulted and examined with an expert assessment of maps of individual development of the child. Children were evaluated anthropometric indicators, the state of the thyroid gland and sexual development. Examination of all children for the presence of endocrine pathologists and confirmation of the diagnosis were carried out on the basis of the Order of the Ministry of Health of Ukraine № 254 of 04.27.2006 "On the approved protocol for the medical support of children for the specialty" Child endocrinology ". Results. Among the total number of children consulted, endocrine pathology was manifested in 36,7 %. The diagnosis of newly diagnosed endocrine pathology was first confirmed in 29,9% of children. Among endocrine pathologists, perovism is occupied by obesity (39,9%), the second – thyroid pathology (36,4%), the third – impaired growth (18,3%), the fourth – impaired sexual development (7,4%). In 40% of cases, a violation of sexual development is combined with a violation of growth. It has been established that primary care doctors in 40–50% of cases do not perform anthropometry for children at all, the state of sexual development is not evaluated in 70% of cases, which leads to an untimely referral to a pediatric endocrinologist and complicates further treatment. Conclusions. A high percentage of children with first diagnosed endocrine pathology at the stage of primary care and the late delivery by doctors of children to a pediatric endocrinologist was established, which is due to the lack of primary care physicians' assessment of anthropometric indicators of the child’s physical development, thyroid and sexual development.